Design an Innovative Smart Control Scheme to Hybridize Conventional and Expert Controllers (International Journal of Engineering and Computer Science, 2018)
The purposes of the proposed research present approaches to the design of an Innovative Smart Control Scheme (SCS) methodology mergers the proposed local controllers (conventional PID and the expert controller such as fuzzy Logic controllers (FLC)) in a smart way. This SCS switching and merging mechanism depends on FLC that monitors the process state and act as a supervisory to make hybrid control between the local controllers. A local controller is an analytical controller designed to work around specific process operation .Once the conditions change, the rule-based supervisor decreases the influence of one classical controller (PI) and gives more weight to another intelligent controller (Fuzzy Logic) that has been designed to work in the new conditions. Application of the suggested (SCS) on a simple plant which could be a resonator in proposed system, DC machine is introduced and better response of the new proposed SCS is presented. The performance of SCS will compared to the FLC and PID. MATLAB/SIMULINK program is projected for Comparison testing by applying different disturbances cases.